Innovating the Iowa Congregate Nutrition Program: A Needs and Preference Assessment. Issue 4 (2nd October 2021) - Schultz, Savannah; Francis, Sarah L.; Russell, Carlene; Getty, Tim; Bauman, Alexandra
Abstract: Participation in the Congregate Nutrition Program (CNP) is declining. This study examined CNP participation motivators, barriers, menu preferences, desired facility attributes, and educational programming to help identify strategies to increase participation. Four focus groups were held (3 = CNP participants only, n  = 21; 1 = non-CNP participants, n  = 11). They were audio-recorded, transcribed, and analyzed for common themes. All participants were White and food secure (93.8%). The majority were educated (75.8%), female (72.2%), and aged 71–80 years old (53.1%). CNP participation motivators were affordability, healthy meals, socialization, and location convenience. CNP participation barriers were limited awareness, the low perceived need for attending the CNP, and transportation. Ideal CNP characteristics were menu choice, variety of activities, and a welcoming ambiance. Preferred marketing strategies were print advertising and word of mouth. These findings provide insight as to how the CNP may be modified to be more appealing for the older adult population.